2007
DOI: 10.1016/j.ydbio.2006.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuous organization and specification of the lateral floor plate in zebrafish

Abstract: The floor plate is a signaling center in the ventral neural tube of vertebrates with important functions during neural patterning and axon guidance. It is composed of a centrally located medial floor plate (MFP) and a bilaterally positioned lateral floor plate (LFP). While the role of the MFP as source of signaling molecules like, e.g., Sonic Hedgehog (Shh) is well understood, the exact organization and function of the LFP are currently unclear. Based on expression analyses, the one cell wide LFP in zebrafish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
94
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(99 citation statements)
references
References 63 publications
4
94
1
Order By: Relevance
“…We tested this using antisense MOs designed to interfere with nkx2.2a translation. Previous work showed that nkx2.2a MOs reduce or eliminate expression of genes that mark cells born within the p3 domain (Schafer et al, 2007;Kucenas et al, 2008). Accordingly, in nkx2.2a MO-injected embryos, olig2 RNA expression expanded ventrally to include cells adjacent to medial floor plate (see Supplementary Fig.…”
Section: Nkx22a Function Is Necessary For Specification and Differenmentioning
confidence: 84%
See 2 more Smart Citations
“…We tested this using antisense MOs designed to interfere with nkx2.2a translation. Previous work showed that nkx2.2a MOs reduce or eliminate expression of genes that mark cells born within the p3 domain (Schafer et al, 2007;Kucenas et al, 2008). Accordingly, in nkx2.2a MO-injected embryos, olig2 RNA expression expanded ventrally to include cells adjacent to medial floor plate (see Supplementary Fig.…”
Section: Nkx22a Function Is Necessary For Specification and Differenmentioning
confidence: 84%
“…nkx2.2a MO1 (5′-CCG TCT TTG TGT TGG TCA ACG ACA T-3′) was complementary to a sequence spanning just before and including the translation start codon (Schafer et al, 2007;Kucenas et al, 2008). nkx2.2a MO2 (5′-AAG TTG CTG CAC CAG TTT GAC AAT C-3′) was complementary to a sequence in the 5′ UTR.…”
Section: Morpholino Injectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Axonal guidance has been studied principally in the spinal cord, where there is a subset of cells in the ventral and dorsal midline, floor plate and roof plate respectively, that secrete several factors involved in axonal guidance (Kennedy et al, 1994;Murakami and Shirasaki, 1997;Matise et al, 1999;Kaprielian et al, 2001). The description of spatially restricted expression of various immunocytochemical and molecular markers in ventral neural tube of several vertebrate species has led to the distinction of two populations of cells in the floor plate: a centrally located medial floor plate (MFP) and a bilaterally positioned lateral floor plate (LFP; Schafer et al, 2007). Thus, in the chick ventral neural tube at Hamburger and Hamilton stage (HH) 20 (Hamburger and Hamilton, 1951), a medial region, where the cells express both SC1 and FP1 antigens, can be distinguished from lateral areas where the cells express FP1 but not SC1 Yamada et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The division between MFP and LFP has functional implications due to the differential expression of axonal guidance cues. In chicken, for instance, the floor plate marker genes sonic hedgehog and netrin-1 are expressed in the LFP, while Foxa2 is transiently restricted to the MFP (Marti et al, 1995;Charrier et al, 2002;Schafer et al, 2007). On the other hand, the cells of the roof plate, located at the dorsal midline, are also specialized in the secretion of molecules that control multiple aspects of the dorsal CNS development, including axonal guidance (Chizhikov and Millen, 2005).…”
Section: Introductionmentioning
confidence: 99%